2015
DOI: 10.1115/1.4029477
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Nonaxisymmetric Endwall Contouring and Three-Dimensional Airfoil Design in a 1.5 Stage Axial Turbine—Part II: Experimental Validation

Abstract: This paper is the second part of a two-part paper reporting on the increase in efficiency of a 1.5 stage axial test rig turbine with the use of nonaxisymmetric endwalls and 3D airfoil design. Contoured endwalls were developed for the inlet guide vane separately, as well as in combination with a bowed radial profile stacking. In addition, a contour endwall was applied to the hub of the unshrouded rotor. In Part I, the design of the profiled endwalls and 3D airfoils is presented, as well as a detailed analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Since the rotor has no shroud and the casing is cylindrical, this improvement must result from a homogenization of the stator outflow, resulting in an improved radial incidence distribution at the rotor inlet. Such a homogenization was in fact reported in previous measurements of this F3D configuration by Niewoehner et al (2015). Above 50% channel height, the purge flow has no effect on the flow, leading to basically congruent curves in both configurations.…”
Section: Numerical Validationsupporting
confidence: 84%
See 1 more Smart Citation
“…Since the rotor has no shroud and the casing is cylindrical, this improvement must result from a homogenization of the stator outflow, resulting in an improved radial incidence distribution at the rotor inlet. Such a homogenization was in fact reported in previous measurements of this F3D configuration by Niewoehner et al (2015). Above 50% channel height, the purge flow has no effect on the flow, leading to basically congruent curves in both configurations.…”
Section: Numerical Validationsupporting
confidence: 84%
“…This end wall optimization was combined with a bowed first stator. Experimental validations by Niewoehner et al (2015) showed that these design choices helped improve the efficiency of the rig by 0.59%.…”
Section: Introductionmentioning
confidence: 99%
“…Germain et al 16 and Schu¨pbach et al 17 designed NAEP for a turbine by using an automatic numerical optimization method, which resulted in reduced secondary flow and an improvement of stage efficiency by 1% AE 0.4%. Poehler et al 18 and Niewoehner et al 19 carried out an investigation of NAEP separately and its combination with bowed blading in a 1.5-stage axial turbine. Significant increase in efficiency for both configurations was observed, and the designs were beneficial under off-design conditions.…”
Section: Introductionmentioning
confidence: 99%
“…18 and Niewoehner et al. 19 carried out an investigation of NAEP separately and its combination with bowed blading in a 1.5-stage axial turbine. Significant increase in efficiency for both configurations was observed, and the designs were beneficial under off-design conditions.…”
Section: Introductionmentioning
confidence: 99%
“…15 and Niewoehner et al. 16 investigated non-axisymmetric endwall profiling and 3D airfoil design in a 1.5-stage axial turbine.…”
Section: Introductionmentioning
confidence: 99%